The Implementation of the Village Financial Information System - Rizki Amalia; Zaldy Adrianto (Journal of Accounting Auditing and Business, 2023)
This research was conducted to determine the implementation of Siskeudes (Sistem Keuangan Desa – Village Financial Information System) by using the updated DeLone and McLean information system success model as a mandatory information system in Villages in Majalengka Regency, West Java. This research examined the impact of the quality of a system, quality of information, and service quality on user satisfaction and the impact of user satisfaction on perceived net benefit. Data were obtained from questionnaires distributed to 65 respondents in Majalengka Regency. The methods used in this study were descriptive analysis with path analysis. The results of this study indicated a significant effect of system quality and the quality of service on user satisfaction and the effect of user satisfaction on perceived net benefits. Still, they showed no significant effects of the quality of information on user satisfaction.The implementation of Siskeudes was classified as a success.